MODERN THERAPY OF CHRONIC HEART FAILURE: IMPORTANCE OF ALDOSTERONE ANTAGONISTS - Yabluchanskіy, N.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The place of aldosterone antagonists in modern therapy of chronic heart failure is considered. It is shown, that the aldosterone antagonists expand influences of angiotensin converting enzyme inhibitors on the renin-aldosterone-angiotensin system, what promotes achievement of more significant steady positive results in medical treatment of patients with heart failure.